2005
DOI: 10.1021/la0503451
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate-Modified Superparamagnetic Nanoparticles and Their Intracellular Uptake into Human Cancer Cells

Abstract: A magnetic nanoparticle conjugate was developed that can potentially serve both as a contrast enhancement agent in magnetic resonance imaging and as a drug carrier in controlled drug delivery, targeted at cancer diagnostics and therapeutics. The conjugate is made of iron oxide nanoparticles covalently bound with methotrexate (MTX), a chemotherapeutic drug that can target many cancer cells whose surfaces are overexpressed by folate receptors. The nanoparticles were first surface-modified with (3-aminopropyl)tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
383
1
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 555 publications
(396 citation statements)
references
References 27 publications
10
383
1
2
Order By: Relevance
“…The second strategy was able to be successfully shown by binding magnetoliposome-antibody complexes to MN antigens of renal cell carcinoma cells [206], magnetoliposomeanti-Her2-AB to breast cancer cells [203], or anti-folate receptor-SPIO to different tumor cell lines [207]. The third strategy was able to be successfully proven on the basis of rhenium188-loaded immuno(hepama-1)magnetic nanoparticles (Re-SPIO-AB) against liver carcinoma cells [208], methotrexate-conjugated SPIO against breast (MCF7) and cervical (HeLa) carcinoma cells [209], doxorubicin-loaded nanomicelles [210], doxorubicin-carrying hyaluronan-SPIO (DOX-HA-SPIO) [211], docetaxel-carboxymethylcellulose-SPIO [212], layer-by-layer (LbL) polyelectrolyte capsules that can be loaded with SPIO and/or therapeutic agents [213], SPIO-and doxorubicin-loaded cetuximab-anti-EGFR immunomicelles or with doxorubicin(liposomal)-loaded macrophages (macrophage-LP-Dox) that accumulate in tumors [214]. Although major advances in tumor labeling and tumor therapy via therapeutic imaging SPIO constructs (theranostics) have been made in recent years, the development of potent in vivo theranostics with high specificity and sensitivity has remained a significant challenge due to the heterogeneity of the expression level of the target structure on the tumor cells and problems with overcoming physiological barriers (e. g. extravasation or blood-tissue barriers) preventing access to the target cell (pharmacological accessibility).…”
Section: Molecular Therapymentioning
confidence: 99%
“…The second strategy was able to be successfully shown by binding magnetoliposome-antibody complexes to MN antigens of renal cell carcinoma cells [206], magnetoliposomeanti-Her2-AB to breast cancer cells [203], or anti-folate receptor-SPIO to different tumor cell lines [207]. The third strategy was able to be successfully proven on the basis of rhenium188-loaded immuno(hepama-1)magnetic nanoparticles (Re-SPIO-AB) against liver carcinoma cells [208], methotrexate-conjugated SPIO against breast (MCF7) and cervical (HeLa) carcinoma cells [209], doxorubicin-loaded nanomicelles [210], doxorubicin-carrying hyaluronan-SPIO (DOX-HA-SPIO) [211], docetaxel-carboxymethylcellulose-SPIO [212], layer-by-layer (LbL) polyelectrolyte capsules that can be loaded with SPIO and/or therapeutic agents [213], SPIO-and doxorubicin-loaded cetuximab-anti-EGFR immunomicelles or with doxorubicin(liposomal)-loaded macrophages (macrophage-LP-Dox) that accumulate in tumors [214]. Although major advances in tumor labeling and tumor therapy via therapeutic imaging SPIO constructs (theranostics) have been made in recent years, the development of potent in vivo theranostics with high specificity and sensitivity has remained a significant challenge due to the heterogeneity of the expression level of the target structure on the tumor cells and problems with overcoming physiological barriers (e. g. extravasation or blood-tissue barriers) preventing access to the target cell (pharmacological accessibility).…”
Section: Molecular Therapymentioning
confidence: 99%
“…Nanoparticles are currently used in imaging, [1][2][3][4][5][6] biosensing, [7][8][9] and gene and drug delivery. [10][11][12] As the field continues to develop, quantitative and qualitative studies on the cellular uptake of nanoparticles, with respect to their size and shape, are required in order to advance nanotechnology for biomedical applications. This will be important for assessing nanoparticle toxicity (i.e., if nanoparticles do not enter cells, they are less prone to killing cells or altering cellular function), for advancing nanoparticles for imaging, drug delivery, and therapeutic applications (i.e., how to maximally accumulate nanoparticles in cells, tumors, and organs?…”
mentioning
confidence: 99%
“…Cellular viability studies in human breast cancer cells (MCF-7) and human cervical cancer cells (HeLa) further demonstrated the effectiveness of such chemical cleavage of MTX inside the target cells through the action of intracellular enzymes. The intracellular trafficking model was supported through nanoparticle uptake studies which demonstrated that the cells expressing the human folate receptors internalized a higher level of nanoparticles than the negative control cells [81].…”
Section: Methotrexate Nanoparticlesmentioning
confidence: 99%